COMPREHENSIVE ASSESSMENT OF INVESTMENT ATTRACTIVENESS OF REGIONS (BASED ON THE EXAMPLE OF THE REGIONS OF THE FAR EAST) - Levkina, Elena; Sakharova, Larisa; Edelev, Dmitry (Revista Inclusiones, 2020)
The increasing role of the subjects of the Russian Federation in the development and implementation of investment initiatives aimed at accelerated development of socio-economic processes in regions through the implementation of investment policy determines the relevance of the topic. Stimulation of investment activity of regions, large regional enterprises, business associations and financial companies is the main task for the achievement of the purpose of economic policy – an increase of the standard of living of the population in the region. To determine the effectiveness of the formation and implementation of investment policy, it is necessary to assess the dynamics of investment attractiveness of regions.